Pemanfaatan Pati Beras Ketan Pragelatinasi sebagai Matriks Tablet Lepas Lambat Natrium Diklofenak - Lukman, Anita; Lucida, Henny; Ben, Elfi Sahlan (Fakultas Farmasi Universitas Andalas, 2012)
A study on the use of pregelatinized glutinous rice starch in combination with sodium carboxy methyl cellulose as sustained release matrix and sodium diclofenac as a model has been conducted. Two formulas were prepared with these ratio of pregelatized glutinous rice starch to Na CMC of (42,70% : 14,25 %) (F1) and (28,5% : 28,5 %) (F2) respectively. Evaluation of pharmaceutical properties of the tablets showed that all formulas fulfilled the requirement in term of weight uniformity, content uniformity, friability, hardness and disintegration time. Dissolution profile showed that F1 showed down the release of drug at 86% in 12 hours, while F2 80,16 % in 12 hours.